Biochemical genetic relationship of Thailand and Hawaii isolates of Parastrongylus cantonensis (Nematoda: Angiostrongylidae) - Eamsobhana, Praphathip; Dechkum, N.; Yong, Hoi Sen (Elsevier, 2008)
The genetic relationship of the Thailand and Hawaii isolates (strains) of the rat lungworm Parastrongylus (=Angiostrongylus) cantonensis was investigated by gene–enzyme systems using vertical polyacrylamide slab gel electrophoresis. Six gene–enzyme systems were successfully determined, with each being represented by two presumptive loci. Glucose phosphate dehydrogenase, glucose phosphate isomerase, lactate dehydrogenase, malate dehydrogenase and malic enzyme were monomorphic at both loci, and the respective bands exhibited similar mobility in both isolates implying absence of genetic variation.